ORGANIZATION OF FRAUD INVESTIGATION IN THE FIELD OF VOLUNTEER AND CHARITY ACTIVITIES OR PROVISION OF HUMANITARIAN AID - Lykhova, Sofiia (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
Review of the monograph by Babikova O.S., Tytor D.P. “Organization of the investigation of fraud in the field of volunteer and charitable activities or the provision of humanitarian aid”. The reviewer notes that this monograph is another modern new and important direction of research into the commission of criminal offenses, which has not yet been considered by other scientists. In terms of its content, the monograph consists of a theoretical and legal analysis and a forensic characterization of fraud in the field of volunteer and charitable activities or the provision of humanitarian aid, which reveals the legal regulation of this area. The greatest attention is paid to the assessment and circumstances of the features of the organization of the investigation of fraud in the field of volunteer and charitable activities or the provision of humanitarian aid, as well as forensic prevention and counteraction to the commission of criminal offenses, their timely detection and immediate adoption of measures to avoid and overcome them. Some attention was paid to the features of conducting individual investigative (search) and other procedural actions. The monograph will be useful both for higher education students and legal professionals, law enforcement agencies and organizations, judges, attorneys, and other practicing lawyers who seek to improve their level of professional competence.